2006
DOI: 10.1017/s0967199406003881
|View full text |Cite
|
Sign up to set email alerts
|

PKA activation in concert with ARIS and asterosap induces the acrosome reaction in starfish

Abstract: The acrosome reaction (AR) is a fundamental event for fertilization, which is induced in concert with acrosome reaction-inducing substance (ARIS) and asterosap, both of which are components of starfish egg jelly (EJ). During the AR, a spermatozoon undergoes a series of physiological changes, such as in intracellular cGMP concentration ([cGMP]i), pHi and intracellular Ca2+ concentration ([Ca2+]i). Affinity purification of cGMP-binding protein resulted in the isolation of a regulatory subunit of the cAMP-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In a previous work, we found that EJ components are responsible for the elevation of intracellular cAMP in starfish spermatozoa and this cAMP subsequently enhanced the PKA activity [6]. Experiments with the PKA-specific antibody suggest a role for PKA on AR, as we have found an increased phosphorylation of some proteins ( Figure 3A).…”
Section: Effects Of Pka Inhibitors On the Kinase Activitysupporting
confidence: 67%
See 3 more Smart Citations
“…In a previous work, we found that EJ components are responsible for the elevation of intracellular cAMP in starfish spermatozoa and this cAMP subsequently enhanced the PKA activity [6]. Experiments with the PKA-specific antibody suggest a role for PKA on AR, as we have found an increased phosphorylation of some proteins ( Figure 3A).…”
Section: Effects Of Pka Inhibitors On the Kinase Activitysupporting
confidence: 67%
“…Sperm protein preparation was done as previously described [6]. Briefly, dry spermatozoa were diluted 1:3 (v/v) in ice-cold lysis buffer, and cells were lysed by a sonicator (Branson Sonifer 250, USA).…”
Section: Preparation Of Sperm Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cAMP enzyme immunoassay, ARIS also increased [cAMP]i in the presence of seawater with high pH (pH 9.5, Islam et al, 2006b). Pretreatment of spermatozoa with two specific, cellpermeable PKA inhibitors, H89 and KT5720, prevented the induction of the AR in a concentration-dependent manner.…”
Section: Protein Kinase Activation Is Involved In Ar Inductionmentioning
confidence: 95%